Presynaptic Mechanisms of l-DOPA-Induced Dyskinesia: The Findings, the Debate, and the Therapeutic Implications - Cenci, M. Angela (Frontiers in Neurology, 2014)
The dopamine precursor L-DOPA has been the most effective treatment for Parkinson´s disease (PD) for over 40 years. However, the response to this treatment changes during the progression of PD, and most patients develop dyskinesias (abnormal involuntary movements) and motor fluctuations within a few years of L-DOPA therapy. There is wide consensus that these motor complications depend on both pre- and post-synaptic disturbances of nigrostriatal dopamine transmission. Several presynaptic mechanisms converge to generate large dopamine swings in the brain concomitant with the peaks-and-troughs of plasma L-DOPA levels, while post-synaptic changes engender abnormal functional responses in dopaminoceptive neurons. While this general picture is well-accepted, the relative contribution of different factors remains a matter of debate. A particularly animated debate has been growing around putative players on the presynaptic side of the cascade. To what extent do presynaptic disturbances in dopamine transmission depend on deficiency/dysfunction of the dopamine transporter, aberrant release of dopamine from serotonin neurons, or gliovascular mechanisms? And does noradrenaline (which is synthetized from dopamine) play a role? This review article will summarize key findings, controversies, and pending questions regarding the presynaptic mechanisms of L-DOPA-induced dyskinesia. Intriguingly, the debate around these mechanisms has spurred research into previously unexplored facets of brain plasticity that have far-reaching implications to the treatment of neuropsychiatric disease.